Resin grinding pad based on LED-UV (Light Emitting Diode-Ultraviolet) photocuring and preparation method thereof
Through the resin grinding pad based on LED-UV light curing, the problems of high cost, unstable cutting force and short service life in the prior art are solved, a low-cost and efficient grinding process is achieved, and the long life and stability of the grinding pad is improved.
Patent Information
- Application Number
- CN202411845693.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
Existing thermal curing or traditional mercury lamp ultraviolet photocuring cured abrasive abrasive pads have problems such as high cost, unstable cutting force and short service life.
Using a resin grinding pad based on LED-UV light curing, the combination of the abrasive material layer, the LED-UV glue curing connection layer, the hard carrier layer and the grinding disc connection layer is used to achieve an efficient photocuring process using raw materials such as photo-solid resin, photocuring monomer, photoinitiator and additive.
A low-cost and efficient grinding process is achieved. The grinding pad has long life, high cutting efficiency and good stability, avoiding the high energy consumption and heat generation problems in traditional technology.
Smart Images

Figure CN119609914A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of superhard material processing, and relates to a diamond grinding pad and a preparation method thereof, and specifically relates to a consolidated abrasive grinding pad based on LED-UV light curing, with a long service life and a high stable cutting rate, and a preparation method thereof. Background Art
[0002] At present, the grinding and polishing of hard and brittle materials such as glass and ceramics mostly adopts the traditional free abrasive processing technology, which has problems such as low grinding efficiency, low abrasive utilization, poor stability, low product yield, and large waste liquid pollution during the processing. The fixed abrasive grinding pad process is used to fix the abrasive in the binder matrix, which effectively avoids the above problems. This process is easy to operate and has high processing efficiency, and has been widely used in the market.
[0003] CN102632453A discloses a thermosetting resin polishing pad and a preparation method thereof, which has the problems of high cost, unstable cutting force and short service life. CN114952608 A discloses a consolidated abrasive polishing pad based on a photo-initiated front-end polymerization reaction and a preparation method thereof, which has the problems of high energy consumption, high heat generation and low utilization rate of the effective spectrum range of traditional UV mercury lamps. Summary of the invention
[0004] In view of the above problems existing in thermally cured or conventional mercury lamp ultraviolet light-cured abrasive polishing pads, the present invention provides a resin polishing pad based on LED-UV light curing and a preparation method thereof. The preparation process of the present invention is simple to operate, has low energy consumption, low cost, and the prepared polishing pad has a long service life, high cutting efficiency, and good processing stability.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A resin polishing pad based on LED-UV light curing, which is composed of a polishing material layer, an LED-UV glue curing connection layer, a hard carrier layer and a grinding disc connection layer in sequence, wherein:
[0007] The grinding material layer is composed of a plurality of abrasive particles, and the abrasive particles are distributed in an array on the surface of the LED-UV glue curing connection layer;
[0008] The abrasive grains are prepared from the following raw materials: 40-50 wt% of a photocurable resin A, 15-25 wt% of a photocurable monomer A, 2-4 wt% of a photoinitiator A, 0.5-2 wt% of an auxiliary agent, 3-10 wt% of an abrasive, and 10-30 wt% of a filler;
[0009] The LED-UV glue curing connection layer is prepared from the following raw materials: 60-70 wt% of light-curable resin B, 25-35 wt% of light-curable monomer B, and 4-5 wt% of photoinitiator B;
[0010] The hard carrier layer is a colorless and transparent PC endurance board;
[0011] The grinding disc connecting layer is double-sided adhesive;
[0012] In the grinding material layer, the photocurable resin A is one or a combination of 2021P alicyclic epoxy acrylate, F-51 novolac epoxy acrylate, and E-51 bisphenol A epoxy acrylate; the photocurable monomer A is one or a combination of PETA (pentaerythritol triacrylate), TMPTA (trimethylolpropane triacrylate), DPHA (dipentaerythritol hexaacrylate), HDDA (hexanediol diacrylate), HEMA (hydroxyethyl methacrylate), and IBOA (isobornyl acrylate); the photoinitiator A is TPO ((2,4,6-trimethylbenzoyl) diphenylphosphine oxide), 819 (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide), 184 (hydroxycyclohexyl phenyl ketone) or a combination thereof; the auxiliary agent is one or a combination of TEGOAirex920, BYK-057, BYK-358N, EFKA-3600; the abrasive is one or a combination of diamond, boron nitride, aluminum oxide; the filler is one or a combination of calcium carbonate, barium sulfate, sericite, magnesium oxide;
[0013] In the grinding material layer, the photocurable resin A is used to fix the abrasive, enhance the holding force of the abrasive, and adjust the wear ratio; the photocurable monomer A is used as an auxiliary resin to adjust the hardness and construction viscosity; the photoinitiator A is used to initiate cross-linking polymerization; the auxiliary agent is used to eliminate bubbles, improve flatness, and enhance curing strength; the filler is used to adjust the curing shrinkage of the system and balance hardness and wear;
[0014] In the LED-UV glue curing connection layer, the photocurable resin B is one or a combination of polyurethane acrylate and caprolactone-modified epoxy acrylate; the photocurable monomer B is one or a combination of HEMA (hydroxyethyl methacrylate), ACMO (acryloyl morpholine), THFA (tetrahydrofuran acrylate), and IBOA (isobornyl acrylate); the photoinitiator B is one or a combination of TPO ((2,4,6-trimethylbenzoyl) diphenylphosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone);
[0015] In the LED-UV glue curing connection layer, the photocurable resin B provides adhesion and water and chemical resistance; the photocurable monomer B serves as an auxiliary resin to adjust the formulation construction viscosity and increase the bonding strength; and the photoinitiator B initiates cross-linking polymerization.
[0016] The thickness of the abrasive grains is 1.79-1.81 mm, the thickness of the LED-UV glue curing connection layer is 0.28-0.32 mm, the thickness of the hard carrier layer is 0.99-1.01 mm, and the thickness of the grinding disc connection layer is 0.18-0.22 mm.
[0017] A method for preparing the above-mentioned resin polishing pad based on LED-UV light curing comprises the following steps:
[0018] Step (1) weighing a photocurable resin A, a photocurable monomer A, a photoinitiator A, an auxiliary agent and a filler in proportion, pouring them into a prepared mixing container, dispersing them mechanically at high speed, and then evenly dispersing the abrasive therein, and vacuum degassing to obtain a uniform and bubble-free linker slurry;
[0019] Step (2) weighing the photocurable resin B, the photocurable monomer B, and the photoinitiator B in proportion, pouring them into a prepared mixing container, mechanically dispersing at high speed, and vacuum degassing to obtain a uniform and bubble-free LED-UV curing glue;
[0020] Step (3) Filling the binder slurry obtained in step (1) into a silicone mold, scraping the surface with a steel scraper to remove excess slurry and make the surface smooth;
[0021] Step (4) The silicone mold filled with the linking material slurry in step (3) is subjected to a 395nm wavelength LED-UV lamp with an energy value of 3000-4000mj / cm 2 Full light curing;
[0022] Step (5) on the flat mold after light curing in step (4), evenly apply a layer of LED-UV curing glue prepared in step (2), and then lay a layer of hard carrier layer, and roll it to make it flat and bubble-free;
[0023] Step (6) The mold coated with the LED-UV glue curing connection layer and the hard carrier layer in step (5) is transported under a 395nm wavelength LED-UV lamp with an energy value of 2000-3000mj / cm 2 Full light curing and demoulding;
[0024] Step (7) coating the back of the demoulding hard carrier layer with a grinding disc bonding layer;
[0025] Step (8) cutting the polishing pad covered with the grinding disc bonding layer into a size suitable for the machine to obtain a resin polishing pad based on LED-UV light curing.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1. The present invention effectively connects all powder materials by adding light-curable resin to the resin polishing pad, so that the resin polishing pad has good strength, good stability and long service life.
[0028] 2. The resin polishing pad based on LED-UV light curing of the present invention has a low cost and can complete the curing process at room temperature. Its production process is simple, effectively solving the problems of high energy consumption and long production time of traditional thermal curing, while avoiding the large amount of heat and ozone hazards generated during ordinary ultraviolet light curing, as well as the limitations on equipment use.
[0029] 3. The present invention reduces the amount of abrasive used and effectively improves the machining accuracy of the workpiece. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The structure diagram of the resin polishing pad based on LED-UV light curing of the present invention is shown in the figure, 1: polishing material layer, 1-1: abrasive grains, 2: LED-UV glue curing connection layer, 3: hard carrier layer, 4: grinding disc connection layer;
[0031] Figure 2 for Figure 1 Top view of the . DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0033] Embodiment 1:
[0034] This embodiment provides a resin polishing pad based on LED-UV light curing, such as Figure 1 and Figure 2 As shown, the resin polishing pad is composed of a polishing material layer 1, an LED-UV glue curing connection layer 2, a hard carrier layer 3 and a grinding disc connection layer 4 in sequence, wherein:
[0035] The grinding material layer 1 is composed of a plurality of abrasive particles 1-1, and the abrasive particles 1-1 are distributed in an array on the surface of the LED-UV glue curing connection layer;
[0036] The abrasive grain 1-1 is formed by LED-UV light-curing resin consolidating diamond abrasive, and is specifically prepared from 50wt% of light-curing resin A, 16wt% of light-curing monomer A, 3wt% of photoinitiator A, 1wt% of auxiliary agent, 10wt% of abrasive, and 20wt% of filler, wherein the abrasive grain specification is 3*3*1.8mm, the gap between the abrasive grains is 1mm, the light-curing resin A is 2021P alicyclic epoxy acrylate; the light-curing monomer A is DP HA (dipentaerythritol hexaacrylate) and HEMA (hydroxyethyl methacrylate), the ratio of the two is 3:1; the photoinitiator A is TPO ((2,4,6-trimethylbenzoyl) diphenylphosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), the ratio of the two is 5:1; the additives are BYK-057 and BYK-358N, the ratio of the two is 1:1; the abrasive is agglomerated 80μm diamond powder; the filler is calcium carbonate and magnesium oxide, the mass ratio of the two is 3:2;
[0037] The LED-UV glue curing connection layer 2 is a 0.3 mm thick LED-UV glue curing film, which is prepared from the following raw materials: 70 wt% of light-curing resin B, 25 wt% of light-curing monomer B, and 5 wt% of photoinitiator B; wherein the light-curing resin B is polyurethane acrylate and caprolactone-modified epoxy acrylate, and the mass ratio of the two is 4:1; the light-curing monomer B is HEMA (hydroxyethyl methacrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:2:2; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1;
[0038] The hard carrier layer 3 is a 1 mm thick colorless transparent PC endurance board;
[0039] The grinding disc connecting layer 4 is 0.2 mm thick 3M9815 double-sided adhesive.
[0040] The specific preparation steps are as follows:
[0041] Step (1) weighing a photocurable resin A, a photocurable monomer A, a photoinitiator A, an auxiliary agent and a filler in proportion, pouring them into a prepared mixing container, dispersing them mechanically at high speed, and then evenly dispersing the abrasive therein, and vacuum degassing to obtain a uniform and bubble-free linker slurry;
[0042] Step (2) weighing the photocurable resin B, the photocurable monomer B, and the photoinitiator B in proportion, pouring them into a prepared mixing container, mechanically dispersing at high speed, and vacuum degassing to obtain a uniform and bubble-free LED-UV curing glue;
[0043] Step (3) Filling the binder slurry obtained in step (1) into a silicone mold, scraping the surface with a steel scraper to remove excess slurry and make the surface smooth;
[0044] Step (4) The silicone mold filled with the linking material slurry in step (3) is subjected to a 395nm wavelength LED-UV lamp with an energy value of 3000-4000mj / cm 2 Full light curing;
[0045] Step (5) on the flat mold after light curing in step (4), evenly apply a layer of LED-UV curing glue prepared in step (2), and then lay a 1 mm thick hard carrier layer, and roll it to make it flat and bubble-free;
[0046] Step (6) The mold coated with the LED-UV glue curing connection layer and the hard carrier layer in step (5) is transported under a 395nm wavelength LED-UV lamp with an energy value of 2000-3000mj / cm 2 After sufficient light curing, the LED-UV light-cured polishing pad can be obtained by demoulding;
[0047] Step (7) coating the back of the hard carrier layer of the LED-UV light-cured polishing pad after demoulding with a grinding disc bonding layer;
[0048] Step (8) cutting the polishing pad covered with the grinding disc bonding layer into a size suitable for the machine to obtain a resin polishing pad based on LED-UV light curing.
[0049] The grinding pad prepared by the above method was measured to have a height of 1.803 mm and a Shore hardness of 92.5 HD. On the Aigu HF-50 tensile tester, the pull-out force of the abrasive was tested to be 105 N. After soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the abrasive was tested to be 88 N. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper plate speed was set to 7 rpm, the lower plate speed was set to 4 rpm, the air pressure was maintained at 0.1 MPa, and deionized water without any abrasive and adjusted to a pH of 9 by ethylenediamine was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 1.8%, the abrasive height of the test grinding pad is 1.658mm, the roughness of the processed K9 glass is 0.9μm, the average thinning rate is 80μm / min, and the grinding pad life is 248.3Hours.
[0050] Embodiment 2:
[0051] The difference between this embodiment and Embodiment 1 is that in the LED-UV glue curing connection layer, the photocurable resin B is polyurethane acrylate and caprolactone modified epoxy acrylate, and the mass ratio of the two is 4:1; the photocurable monomer B is HEMA (hydroxyethyl methacrylate), THFA (tetrahydrofuran acrylate), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:1:3; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1.
[0052] The grinding pad prepared by the above method measured the abrasive height of 1.800mm and the Shore hardness of 92.5HD. On the Aigu HF-50 tensile tester, the pull-out force of the tested abrasive was 108N. After soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the tested abrasive was 95N. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper plate speed was set to 7rpm, the lower plate speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as the grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reached 1200 minutes, the abrasive drop rate was 1.5%, the test grinding pad abrasive height was 1.657mm, the roughness of the processed K9 glass was 0.9μm, the average thinning rate was 78μm / min, and the grinding pad life was 251.7Hours.
[0053] Embodiment 3:
[0054] The difference between this embodiment and embodiment 1 is that in the LED-UV glue curing connection layer, the photocurable resin B is polyurethane acrylate and caprolactone modified epoxy acrylate, and the mass ratio of the two is 6:1; the photocurable monomer B is HEMA (hydroxyethyl methacrylate), THFA (tetrahydrofuran acrylate), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:1:3; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1.
[0055] The grinding pad prepared by the above method was measured to have an abrasive height of 1.801 mm and a Shore hardness of 92.5 HD. On the Aigu HF-50 tensile tester, the pull-out force of the abrasive was tested to be 127 N. After soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the abrasive was tested to be 109 N. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper plate speed was set to 7 rpm, the lower plate speed was set to 4 rpm, the air pressure was maintained at 0.1 MPa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 1.2%, the abrasive height of the test grinding pad is 1.660mm, the roughness of the processed K9 glass is 0.9μm, the average thinning rate is 78μm / min, and the grinding pad life is 255.3Hours.
[0056] Embodiment 4:
[0057] The difference between this embodiment and embodiment 1 is that in the LED-UV glue curing connection layer, the photocurable resin B is polyurethane acrylate and caprolactone modified epoxy acrylate, and the mass ratio of the two is 6:1; the photocurable monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:2:2; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1.
[0058] The grinding pad prepared by the above method was measured to have an abrasive height of 1.800mm and a Shore hardness of 92.5HD. On the Aigu HF-50 tensile tester, the pull-out force of the abrasive was tested to be 128N. After soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the abrasive was tested to be 111N. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7rpm, the lower disc speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0.8%, the abrasive height of the test grinding pad is 1.660mm, the roughness of the processed K9 glass is 0.9μm, the average thinning rate is 80μm / min, and the grinding pad life is 257.1Hours.
[0059] Embodiment 5:
[0060] The present embodiment is different from the embodiment 1 in that the LED-UV glue curing connection layer is prepared from the following raw materials: 66wt% of photocurable resin B, 30wt% of photocurable monomer B, and 4wt% of photoinitiator B; wherein the photocurable resin B is polyurethane acrylate; the photocurable monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:2:2; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 3:1.
[0061] The grinding pad prepared by the above method was measured to have an abrasive height of 1.799 mm and a Shore hardness of 92.5 HD. On the Aigu HF-50 tensile tester, the pull-out force of the tested abrasive was 136 N, and the hard carrier layer PC board was damaged in a filamentous manner and fell off together with the particles. After soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the tested abrasive was 128 N, and the hard carrier layer PC board was damaged in a filamentous manner and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7 rpm, the lower disc speed was set to 4 rpm, the air pressure was maintained at 0.1 MPa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0.3%, the abrasive height of the test grinding pad is 1.658mm, the roughness of the processed K9 glass is 0.9μm, the average thinning rate is 77μm / min, and the grinding pad life is 255.3Hours.
[0062] Embodiment 6:
[0063] The difference between this embodiment and embodiment 1 is that in the LED-UV glue curing connection layer, the photocurable resin B is polyurethane acrylate; the photocurable monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:1:3; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 3:1.
[0064] The grinding pad prepared by the above method was measured to have an abrasive height of 1.801mm and a Shore hardness of 92.5HD. On the Aigu HF-50 tensile tester, the pull-out force of the test abrasive was 138N, and the hard carrier layer PC board was damaged in a filamentous manner and fell off together with the particles. After soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the test abrasive was 128N, and the hard carrier layer PC board was damaged in a filamentous manner and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7rpm, the lower disc speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0.1%, the abrasive height of the test grinding pad is 1.658mm, the roughness of the processed K9 glass is 0.9μm, the average thinning rate is 79μm / min, and the grinding pad life is 251.7Hours.
[0065] Embodiment 7:
[0066] The difference between this embodiment and embodiment 1 is that in the LED-UV glue curing connection layer, the photocurable resin B is polyurethane acrylate; the photocurable monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:2:4; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1.
[0067] The grinding pad prepared by the above method was measured to have an abrasive height of 1.800mm and a Shore hardness of 92.5HD. On the Aigu HF-50 tensile tester, the pull-out force of the test abrasive was 158N, and the hard carrier layer PC board was damaged in a pit shape and fell off together with the particles; after soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the test abrasive was 153N, and the hard carrier layer PC board was damaged in a pit shape and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7rpm, the lower disc speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as the grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0, the abrasive height of the test grinding pad is 1.656mm, the roughness of the processed K9 glass is 0.9μm, the average thinning rate is 80μm / min, and the grinding pad life is 250Hours.
[0068] Embodiment 8:
[0069] The present embodiment is different from the embodiment 1 in that the LED-UV glue curing connection layer is prepared from the following raw materials: 60wt% of photocurable resin B, 35wt% of photocurable monomer B, and 5wt% of photoinitiator B; wherein the photocurable resin B is polyurethane acrylate; the photocurable monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:1:5; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1.
[0070] The grinding pad prepared by the above method was measured to have an abrasive height of 1.799 mm and a Shore hardness of 92.5 HD. On the Aigu HF-50 tensile tester, the pull-out force of the tested abrasive was 160 N, and the hard carrier layer PC board was damaged in the shape of pits and fell off together with the particles; after soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the tested abrasive was 160 N, and the hard carrier layer PC board was damaged in the shape of pits and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7 rpm, the lower disc speed was set to 4 rpm, the air pressure was maintained at 0.1 MPa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as the grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0, the abrasive height of the test grinding pad is 1.658mm, the roughness of the processed K9 glass is 0.9μm, the average thinning rate is 77μm / min, and the grinding pad life is 255.3Hours.
[0071] Embodiment 9:
[0072] The difference between this embodiment and embodiment 8 is that the 2021P alicyclic epoxy acrylate in the grinding material layer is replaced by F-51 phenolic epoxy acrylate.
[0073] The grinding pad prepared by the above method was measured to have an abrasive height of 1.802 mm and a Shore hardness of 94.5 HD. On the Aigu HF-50 tensile tester, the pull-out force of the tested abrasive was 162 N, and the hard carrier layer PC board was damaged in the shape of a pit and fell off together with the particles; after soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the tested abrasive was 161 N, and the hard carrier layer PC board was damaged in the shape of a pit and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7 rpm, the lower disc speed was set to 4 rpm, the air pressure was maintained at 0.1 MPa, and deionized water with a pH value of 9 adjusted with ethylenediamine and containing no abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0, the abrasive height of the test grinding pad is 1.681mm, the roughness of the processed K9 glass is 1.2μm, the average thinning rate is 110μm / min, and the grinding pad life is 297.5Hours.
[0074] Embodiment 10:
[0075] The difference between this embodiment and embodiment 8 is that the 2021P alicyclic epoxy acrylate in the grinding material layer is replaced with E-51 bisphenol A epoxy acrylate.
[0076] The grinding pad prepared by the above method was measured to have an abrasive height of 1.803mm and a Shore hardness of 91HD. On the Aigu HF-50 tensile tester, the pull-out force of the tested abrasive was 160N, and the hard carrier layer PC board was damaged in the shape of pits and fell off together with the particles; after soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the tested abrasive was 160N, and the hard carrier layer PC board was damaged in the shape of pits and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7rpm, the lower disc speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reached 1200 minutes, the abrasive height of the test grinding pad was 1.676 mm, the roughness of the processed K9 glass was 1.1 μm, the average thinning rate was 98 μm / min, and the life of the grinding pad was 283.5 hours.
[0077] Embodiment 11
[0078] This embodiment provides a resin polishing pad based on LED-UV light curing, such as Figure 1 As shown, the resin polishing pad is composed of a polishing material layer 1, an LED-UV glue curing connection layer 2, a hard carrier layer 3 and a grinding disc connection layer 4 in sequence, wherein:
[0079] The grinding material layer 1 is composed of a plurality of abrasive particles 1-1, and the abrasive particles 1-1 are distributed in an array on the surface of the LED-UV glue curing connection layer;
[0080] The abrasive grain 1-1 is formed by LED-UV light-curing resin consolidating diamond abrasive, and is specifically prepared from 40wt% of light-curing resin A, 16wt% of light-curing monomer A, 3wt% of photoinitiator A, 1wt% of auxiliary agent, 10wt% of abrasive, and 30wt% of filler, wherein the abrasive grain specification is 3*3*1.8mm, the gap between the abrasive grains is 1mm, the light-curing resin A is F-51 phenolic epoxy acrylate, the light-curing monomer A is PETA (pentaerythritol triacrylate) and IBOA (isobornyl acrylate), and the mass ratio of the two is 2:1, the photoinitiator A is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1, and the auxiliary agent is TEGO Airex920 and BYK-358N, the mass ratio of the two is 2:3, the abrasive is agglomerated 80μm diamond powder, and the filler is barium sulfate and sericite, the mass ratio of the two is 2:1;
[0081] The LED-UV glue curing connection layer 2 is a 0.3 mm thick LED-UV glue curing film, which is prepared from the following raw materials: 60 wt% of light-curing resin B, 35 wt% of light-curing monomer B, and 5 wt% of photoinitiator B; wherein the light-curing resin B is polyurethane acrylate; the light-curing monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:1:5; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1;
[0082] The hard carrier layer 3 is a 1 mm thick colorless transparent PC endurance board;
[0083] The grinding disc connecting layer 4 is 0.2 mm thick 3M9815 double-sided adhesive.
[0084] The specific preparation steps are as follows:
[0085] Step (1) weighing a photocurable resin A, a photocurable monomer A, a photoinitiator A, an auxiliary agent and a filler in proportion, pouring them into a prepared mixing container, dispersing them mechanically at high speed, and then evenly dispersing the abrasive therein, and vacuum degassing to obtain a uniform and bubble-free linker slurry;
[0086] Step (2) weighing the photocurable resin B, the photocurable monomer B, and the photoinitiator B in proportion, pouring them into a prepared mixing container, mechanically dispersing at high speed, and vacuum degassing to obtain a uniform and bubble-free LED-UV curing glue;
[0087] Step (3) Filling the binder slurry obtained in step (1) into a silicone mold, scraping the surface with a steel scraper to remove excess slurry and make the surface smooth;
[0088] Step (4) The silicone mold filled with the linking material slurry in step (3) is subjected to a 395nm wavelength LED-UV lamp with an energy value of 3000-4000mj / cm 2 Full light curing;
[0089] Step (5) on the flat mold after light curing in step (4), evenly apply a layer of LED-UV curing glue prepared in step (2), and then lay a 1 mm thick hard carrier layer, and roll it to make it flat and bubble-free;
[0090] Step (6) The mold coated with the LED-UV glue curing connection layer and the hard carrier layer in step (5) is transported under a 395nm wavelength LED-UV lamp with an energy value of 2000-3000mj / cm 2 After sufficient light curing, the LED-UV light-cured polishing pad can be obtained by demoulding;
[0091] Step (7) coating the back of the hard carrier layer of the LED-UV light-cured polishing pad after demoulding with a grinding disc bonding layer;
[0092] Step (8) cutting the polishing pad covered with the grinding disc bonding layer into a size suitable for the machine to obtain a resin polishing pad based on LED-UV light curing.
[0093] The grinding pad prepared by the above method was measured to have an abrasive height of 1.800mm and a Shore hardness of 93.5HD. On the Aigu HF-50 tensile tester, the pull-out force of the test abrasive was 163N, and the hard carrier layer PC board was damaged in a pit shape and fell off together with the particles; after soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the test abrasive was 161N, and the hard carrier layer PC board was damaged in a pit shape and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7rpm, the lower disc speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. After the cumulative time reached 1200 minutes, the abrasive height of the test grinding pad was 1.673 mm, the roughness of the processed K9 glass was 0.8 μm, the average thinning rate was 88 μm / min, and the life of the grinding pad was 283.5 hours.
[0094] Example 12
[0095] The difference between this embodiment and embodiment 11 is that the agglomerated 80 μm diamond micropowder is replaced with 80 μm boron nitride micropowder.
[0096] The grinding pad prepared by the above method measured the abrasive height of 1.803mm and the Shore hardness of 93.5HD. On the Aigu HF-50 tensile tester, the pull-out force of the test abrasive was 160N, and the hard carrier layer PC board was damaged in the shape of pits and fell off together with the particles; after soaking in the grinding and cutting fluid with a pH of 12 for 168 hours, the pull-out force of the test abrasive was 160N, and the hard carrier layer PC board was damaged in the shape of pits and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper plate speed was set to 7rpm, the lower plate speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as the grinding and cutting fluid. The single grinding time was 10 minutes, and the thinning value was tested. When the cumulative time reached 600 minutes, the abrasive drop rate was 0, the roughness of the processed K9 glass was 0.2μm, and the average thinning rate was 10μm / min. The thinning efficiency was too low, so the test was stopped.
[0097] Embodiment 13
[0098] This embodiment provides a resin polishing pad based on LED-UV light curing, such as Figure 1 As shown, the resin polishing pad is composed of a polishing material layer 1, an LED-UV glue curing connection layer 2, a hard carrier layer 3 and a grinding disc connection layer 4 in sequence, wherein:
[0099] The grinding material layer 1 is composed of a plurality of abrasive particles 1-1, and the abrasive particles 1-1 are distributed in an array on the surface of the LED-UV glue curing connection layer;
[0100] The abrasive grain 1-1 is formed by consolidating diamond abrasive with LED-UV light-curing resin, and is specifically prepared from 45wt% of light-curing resin A, 18wt% of light-curing monomer A, 4wt% of photoinitiator A, 1wt% of auxiliary agent, 14wt% of abrasive, and 18wt% of filler, wherein the abrasive grain specification is 3*3*1.8mm, the gap between the abrasive grains is 1mm, the light-curing resin A is F-51 phenolic epoxy acrylate, the light-curing monomer A is DPHA (dipentaerythritol hexaacrylate) and IBOA (isobornyl acrylate), and the mass ratio of the two is 3:1; the photoinitiator A is 819 (phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 3:1; the auxiliary agent is TEGO Airex920 and EFKA-3600, the mass ratio of the two is 1:1; the abrasive is agglomerated 80μm diamond powder and aluminum oxide, the mass ratio of the two is 8:6, and the filler is sericite;
[0101] The LED-UV glue curing connection layer 2 is a 0.3 mm thick LED-UV glue curing film, which is prepared from the following raw materials: 60 wt% of light-curing resin B, 35 wt% of light-curing monomer B, and 5 wt% of photoinitiator B; wherein the light-curing resin B is polyurethane acrylate; the light-curing monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:1:5; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1;
[0102] The hard carrier layer 3 is a 1 mm thick colorless transparent PC endurance board;
[0103] The grinding disc connecting layer 4 is 0.2 mm thick 3M9815 double-sided adhesive.
[0104] The specific preparation steps are as follows:
[0105] Step (1) weighing a photocurable resin A, a photocurable monomer A, a photoinitiator A, an auxiliary agent and a filler in proportion, pouring them into a prepared mixing container, dispersing them mechanically at high speed, and then evenly dispersing the abrasive therein, and vacuum degassing to obtain a uniform and bubble-free linker slurry;
[0106] Step (2) weighing the photocurable resin B, the photocurable monomer B, and the photoinitiator B in proportion, pouring them into a prepared mixing container, mechanically dispersing at high speed, and vacuum degassing to obtain a uniform and bubble-free LED-UV curing glue;
[0107] Step (3) Filling the binder slurry obtained in step (1) into a silicone mold, scraping the surface with a steel scraper to remove excess slurry and make the surface smooth;
[0108] Step (4) The silicone mold filled with the linking material slurry in step (3) is subjected to a 395nm wavelength LED-UV lamp with an energy value of 3000-4000mj / cm 2 Full light curing;
[0109] Step (5) on the flat mold after light curing in step (4), evenly apply a layer of LED-UV curing glue prepared in step (2), and then lay a 1 mm thick hard carrier layer, and roll it to make it flat and bubble-free;
[0110] Step (6) The mold coated with the LED-UV glue curing connection layer and the hard carrier layer in step (5) is transported under a 395nm wavelength LED-UV lamp with an energy value of 2000-3000mj / cm 2 After sufficient light curing, the LED-UV light-cured polishing pad can be obtained by demoulding;
[0111] Step (7) coating the back of the hard carrier layer of the LED-UV light-cured polishing pad after demoulding with a grinding disc bonding layer;
[0112] Step (8) cutting the polishing pad covered with the grinding disc bonding layer into a size suitable for the machine to obtain a resin polishing pad based on LED-UV light curing.
[0113] The grinding pad prepared by the above method was measured to have an abrasive height of 1.798 mm and a Shore hardness of 95 HD. On the Aigu HF-50 tensile tester, the pull-out force of the tested abrasive was 161 N, and the hard carrier layer PC board was damaged in the shape of pits and fell off together with the particles; after soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the tested abrasive was 161 N, and the hard carrier layer PC board was damaged in the shape of pits and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper disc speed was set to 7 rpm, the lower disc speed was set to 4 rpm, the air pressure was maintained at 0.1 MPa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the glass thinning value was tested. After the cumulative time reached 1200 minutes, the abrasive height of the test grinding pad was 1.668mm, the roughness of the processed K9 glass was 1.1μm, the average thinning rate was 107μm / min, and the life of the grinding pad was 277Hours.
[0114] Embodiment 14
[0115] This embodiment provides a resin polishing pad based on LED-UV light curing, such as Figure 1 As shown, the resin polishing pad is composed of a polishing material layer 1, an LED-UV glue curing connection layer 2, a hard carrier layer 3 and a grinding disc connection layer 4 in sequence, wherein:
[0116] The grinding material layer 1 is composed of a plurality of abrasive particles 1-1, and the abrasive particles 1-1 are distributed in an array on the surface of the LED-UV glue curing connection layer;
[0117] The abrasive grain 1-1 is formed by LED-UV light-curing resin consolidating diamond abrasive, and is specifically prepared from 45wt% of light-curing resin A, 18wt% of light-curing monomer A, 4wt% of photoinitiator A, 1wt% of auxiliary agent, 14wt% of abrasive, and 18wt% of filler, wherein the abrasive grain specification is 3*3*1.8mm, the gap between the abrasive grains is 1mm, the light-curing resin A is F-51 phenolic epoxy acrylate; the light-curing monomer A is TMPTA (trimethylolpropane triacrylate) and HDDA (hexanediol diacrylate), and the mass ratio of the two is 1:1; the photoinitiator A is 819 (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 3:1; the auxiliary agent is TEGO Airex920 and BYK-358N, the mass ratio of the two is 2:3; the abrasive is agglomerated 80μm diamond powder and aluminum oxide, the mass ratio of the two is 8:6, and the filler is sericite;
[0118] The LED-UV glue curing connection layer 2 is a 0.3 mm thick LED-UV glue curing film, which is prepared from the following raw materials: 60 wt% of light-curing resin B, 35 wt% of light-curing monomer B, and 5 wt% of photoinitiator B; wherein the light-curing resin B is polyurethane acrylate; the light-curing monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:1:5; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenylphosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1;
[0119] The hard carrier layer 3 is a 1 mm thick colorless transparent PC endurance board;
[0120] The grinding disc connecting layer 4 is 0.2 mm thick 3M9815 double-sided adhesive.
[0121] The specific preparation steps are as follows:
[0122] Step (1) weighing a photocurable resin A, a photocurable monomer A, a photoinitiator A, an auxiliary agent and a filler in proportion, pouring them into a prepared mixing container, dispersing them mechanically at high speed, and then evenly dispersing the abrasive therein, and vacuum degassing to obtain a uniform and bubble-free linker slurry;
[0123] Step (2) weighing the photocurable resin B, the photocurable monomer B, and the photoinitiator B in proportion, pouring them into a prepared mixing container, mechanically dispersing at high speed, and vacuum degassing to obtain a uniform and bubble-free LED-UV curing glue;
[0124] Step (3) Filling the binder slurry obtained in step (1) into a silicone mold, scraping the surface with a steel scraper to remove excess slurry and make the surface smooth;
[0125] Step (4) The silicone mold filled with the linking material slurry in step (3) is subjected to a 395nm wavelength LED-UV lamp with an energy value of 3000-4000mj / cm 2 Full light curing;
[0126] Step (5) on the flat mold after light curing in step (4), evenly apply a layer of LED-UV curing glue prepared in step (2), and then lay a 1 mm thick hard carrier layer, and roll it to make it flat and bubble-free;
[0127] Step (6) The mold coated with the LED-UV glue curing connection layer and the hard carrier layer in step (5) is transported under a 395nm wavelength LED-UV lamp with an energy value of 2000-3000mj / cm 2 After sufficient light curing, the LED-UV light-cured polishing pad can be obtained by demoulding;
[0128] Step (7) coating the back of the hard carrier layer of the LED-UV light-cured polishing pad after demoulding with a grinding disc bonding layer;
[0129] Step (8) cutting the polishing pad covered with the grinding disc bonding layer into a size suitable for the machine to obtain a resin polishing pad based on LED-UV light curing.
[0130] The grinding pad prepared by the above method was measured to have a height of 1.801 mm and a Shore hardness of 92 HD. On the Aigu HF-50 tensile tester, the pull-out force of the test abrasive was 160 N, and the hard carrier layer PC board was damaged in a pit shape and fell off together with the particles; after soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the test abrasive was 160 N, and the hard carrier layer PC board was damaged in a pit shape and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper plate speed was set to 7 rpm, the lower plate speed was set to 4 rpm, the air pressure was maintained at 0.1 MPa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the glass thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0, the abrasive height of the test grinding pad is 1.659mm, the roughness of the processed K9 glass is 0.7μm, the average thinning rate is 57μm / min, and the grinding pad life is 253.5Hours.
[0131] Embodiment 15
[0132] This embodiment provides a resin polishing pad based on LED-UV light curing, such as Figure 1 As shown, the resin polishing pad is composed of a polishing material layer 1, an LED-UV glue curing connection layer 2, a hard carrier layer 3 and a grinding disc connection layer 4 in sequence, wherein:
[0133] The grinding material layer 1 is composed of a plurality of abrasive particles 1-1, and the abrasive particles 1-1 are distributed in an array on the surface of the LED-UV glue curing connection layer;
[0134] The abrasive grain 1-1 is formed by LED-UV light-curing resin consolidating diamond abrasive, and is specifically prepared from 43wt% of light-curing resin A, 25wt% of light-curing monomer A, 2.5wt% of photoinitiator A, 0.5wt% of auxiliary agent, 8wt% of abrasive, and 21wt% of filler, wherein the abrasive grain specification is 3*3*1.8mm, the gap between the abrasive grains is 1mm, and the light-curing resin A is F-51 phenolic epoxy acrylate and 2021P alicyclic epoxy acrylate, and the mass ratio of the two is 28:15; photocuring monomer A is DPHA (dipentaerythritol hexaacrylate) and IBOA (isobornyl acrylate), the mass ratio of the two is 3:1; photoinitiator A is 819 (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide) and TPO ((2,4,6-trimethylbenzoyl) diphenyl phosphine oxide), the mass ratio of the two is 2:3; auxiliary agent is EFKA-3600, abrasive is agglomerated 80μm diamond powder, filler is calcium carbonate and sericite, the mass ratio of the two is 1:2;
[0135] The LED-UV glue curing connection layer 2 is a 0.3 mm thick LED-UV glue curing film, which is prepared from the following raw materials: 60 wt% of light-curing resin B, 35 wt% of light-curing monomer B, and 5 wt% of photoinitiator B; wherein the light-curing resin B is polyurethane acrylate; the light-curing monomer B is THFA (tetrahydrofuran acrylate), ACMO (acryloyl morpholine), and IBOA (isobornyl acrylate), and the mass ratio of the three is 1:1:5; the photoinitiator B is TPO ((2,4,6-trimethylbenzoyl) diphenylphosphine oxide) and 184 (hydroxycyclohexyl phenyl ketone), and the mass ratio of the two is 4:1;
[0136] The hard carrier layer 3 is a 1 mm thick colorless transparent PC endurance board;
[0137] The grinding disc connecting layer 4 is 0.2 mm thick 3M9815 double-sided adhesive.
[0138] The specific preparation steps are as follows:
[0139] Step (1) weigh the photocurable resin A, the photocurable monomer A, the photoinitiator A, the auxiliary agent and the filler according to a certain proportion, pour them into a prepared mixing container, disperse them mechanically at high speed, and then evenly disperse the abrasive therein.
[0140] Vacuum degassing to obtain uniform and bubble-free bonding material slurry;
[0141] Step (2) weighing the photocurable resin B, the photocurable monomer B, and the photoinitiator B in proportion, pouring them into a prepared mixing container, mechanically dispersing at high speed, and vacuum degassing to obtain a uniform and bubble-free LED-UV curing glue;
[0142] Step (3) Filling the binder slurry obtained in step (1) into a silicone mold, scraping the surface with a steel scraper to remove excess slurry and make the surface smooth;
[0143] Step (4) The silicone mold filled with the linking material slurry in step (3) is subjected to a 395nm wavelength LED-UV lamp with an energy value of 3000-4000mj / cm 2 Full light curing;
[0144] Step (5) on the flat mold after light curing in step (4), evenly apply a layer of LED-UV curing glue prepared in step (2), and then lay a 1 mm thick hard carrier layer, and roll it to make it flat and bubble-free;
[0145] Step (6) The mold coated with the LED-UV glue curing connection layer and the hard carrier layer in step (5) is transported under a 395nm wavelength LED-UV lamp with an energy value of 2000-3000mj / cm 2After sufficient light curing, the LED-UV light-cured polishing pad can be obtained by demoulding;
[0146] Step (7) coating the back of the hard carrier layer of the LED-UV light-cured polishing pad after demoulding with a grinding disc bonding layer;
[0147] Step (8) cutting the polishing pad covered with the grinding disc bonding layer into a size suitable for the machine to obtain a resin polishing pad based on LED-UV light curing.
[0148] The grinding pad prepared by the above method was measured to have a height of 1.802 mm and a Shore hardness of 95 HD. On the Aigu HF-50 tensile tester, the pull-out force of the test abrasive was 163 N, and the hard carrier layer PC board was damaged in a pit shape and fell off together with the particles; after soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the test abrasive was 161 N, and the hard carrier layer PC board was damaged in a pit shape and fell off together with the particles. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper plate speed was set to 7 rpm, the lower plate speed was set to 4 rpm, the air pressure was maintained at 0.1 MPa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the glass thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0, the abrasive height of the test grinding pad is 1.664mm, the roughness of the processed K9 glass is 1.0μm, the average thinning rate is 106μm / min, and the grinding pad life is 260.9Hours.
[0149] Comparative Example 1:
[0150] A thermosetting resin grinding pad is available on the market, with an effective height of 1.205mm and a Shore hardness of 85HD. On the Aigu HF-50 tensile tester, the pull-out force of the abrasive was tested to be 120N. After soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the abrasive was tested to be 114N. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper plate speed was set to 7rpm, the lower plate speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH value of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the glass thinning value was tested. After the cumulative time reached 1200 minutes, the abrasive drop rate was 0.3%, the test grinding pad abrasive height was 1.013mm, the roughness of the processed K9 glass was 1.1μm, the average thinning rate was 65μm / min, and the grinding pad life was 125Hours.
[0151] Comparative Example 2:
[0152] A common photocurable resin polishing pad on the market has an effective height of 1.202mm and a Shore hardness of 90HD. On the Aigu HF-50 tensile tester, the pull-out force of the abrasive was tested to be 136N. After soaking in a grinding aid cutting fluid with a pH of 12 for 168 hours, the pull-out force of the abrasive was tested to be 133N. The K9 quartz glass plate was ground on the ZK-9B flat grinder of Dongguan Jinyan Company. The upper plate speed was set to 7rpm, the lower plate speed was set to 4rpm, the air pressure was maintained at 0.1Mpa, and deionized water with a pH of 9 adjusted by ethylenediamine without any abrasive was used as a grinding aid cutting fluid. The single grinding time was 10 minutes, and the glass thinning value was tested. After the cumulative time reaches 1200 minutes, the abrasive drop rate is 0.2%, the abrasive height of the test grinding pad is 1.035mm, the roughness of the processed K9 glass is 1.1μm, the average thinning rate is 78μm / min, and the grinding pad life is 143.7Hours.
[0153] The above test results show that compared with traditional thermal curing and ordinary light curing, diamond grinding pads based on LED-UV light-curing resin bonds have higher hardness, comparable processing accuracy, higher abrasive thickness and excellent water and chemical resistance, which bring obvious advantages in long life.
Claims
1. A resin polishing pad based on LED-UV light curing, characterized in that The grinding pad is composed of a grinding material layer, an LED-UV glue curing connection layer, a hard carrier layer and a grinding disc connection layer in sequence. The grinding material layer is composed of a plurality of abrasive particles, and the abrasive particles are distributed in an array on the surface of the LED-UV glue curing connection layer.
2. The resin polishing pad based on LED-UV light curing according to claim 1, characterized in that The thickness of the abrasive grains is 1.79-1.81 mm, the thickness of the LED-UV glue curing connection layer is 0.28-0.32 mm, the thickness of the hard carrier layer is 0.99-1.01 mm, and the thickness of the grinding disc connection layer is 0.18-0.22 mm.
3. The LED-UV light-cured resin polishing pad according to claim 1 or 2, characterized in that The abrasive particles are prepared from the following raw materials: 40-50wt% of a photocurable resin A, 15-25wt% of a photocurable monomer A, 2-4wt% of a photoinitiator A, 0.5-2wt% of an auxiliary agent, 3-10wt% of an abrasive, and 10-30wt% of a filler.
4. The LED-UV light-cured resin polishing pad according to claim 3, characterized in that The photocurable resin A is one or more of alicyclic epoxy acrylate, novolac epoxy acrylate, and bisphenol A epoxy acrylate; the photocurable monomer A is one or more of pentaerythritol triacrylate, trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, hexanediol diacrylate, hydroxyethyl methacrylate, and isobornyl acrylate; the photoinitiator A is one or more of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, phenyl bis(2,4,6-trimethylbenzoyl) phosphine oxide, and hydroxycyclohexyl phenyl ketone; the auxiliary agent is one or more of TEGO Airex920, BYK-057, BYK-358N, and EFKA-3600; the abrasive is one or more of diamond, boron nitride, and aluminum oxide; the filler is one or more of calcium carbonate, barium sulfate, sericite, and magnesium oxide.
5. The LED-UV light-cured resin polishing pad according to claim 1 or 2, characterized in that The LED-UV glue curing connection layer is prepared from the following raw materials: 60-70 wt % of light-curing resin B, 25-35 wt % of light-curing monomer B, and 4-5 wt % of photoinitiator B.
6. The resin polishing pad based on LED-UV light curing according to claim 5, characterized in that The photocurable resin B is one or a combination of polyurethane acrylate and caprolactone-modified epoxy acrylate; the photocurable monomer B is one or a combination of hydroxyethyl methacrylate, acryloylmorpholine, tetrahydrofuran acrylate, and isobornyl acrylate; the photoinitiator B is one or a combination of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide and hydroxycyclohexyl phenyl ketone.
7. The LED-UV light-cured resin polishing pad according to claim 1 or 2, characterized in that The hard carrier layer is a PC solid board.
8. The LED-UV light-cured resin polishing pad according to claim 1 or 2, characterized in that The grinding disc connecting layer is a double-sided adhesive.
9. A method for preparing a resin polishing pad based on LED-UV light curing according to any one of claims 1 to 8, characterized in that The method comprises the following steps: Step (1) weighing a photocurable resin A, a photocurable monomer A, a photoinitiator A, an auxiliary agent and a filler in proportion, pouring them into a prepared mixing container, dispersing them mechanically at high speed, and then evenly dispersing the abrasive therein, and vacuum degassing to obtain a uniform and bubble-free linker slurry; Step (2) weighing the photocurable resin B, the photocurable monomer B, and the photoinitiator B in proportion, pouring them into a prepared mixing container, mechanically dispersing at high speed, and vacuum degassing to obtain a uniform and bubble-free LED-UV curing glue; Step (3) Filling the binder slurry obtained in step (1) into a silicone mold, scraping the surface with a scraper to remove excess slurry and make the surface smooth; Step (4) The silicone mold filled with the linking material slurry in step (3) is subjected to a 395nm wavelength LED-UV lamp with an energy value of 3000-4000mj / cm 2 Full light curing; Step (5) on the flat mold after light curing in step (4), evenly apply a layer of LED-UV curing glue prepared in step (2), and then lay a layer of hard carrier layer, and roll it to make it flat and bubble-free; Step (6) The mold coated with the LED-UV glue curing connection layer and the hard carrier layer in step (5) is transported under a 395nm wavelength LED-UV lamp with an energy value of 2000-3000mj / cm 2 Full light curing and demoulding; Step (7) coating the back of the demoulding hard carrier layer with a grinding disc bonding layer; Step (8) cutting the polishing pad covered with the grinding disc bonding layer into a size suitable for the machine to obtain a resin polishing pad based on LED-UV light curing.
Citation Information
Patent Citations
Thermosetting resin grinding pad and preparation method thereof
CN102632453A
Consolidated abrasive grinding pad based on photo-initiation front-end polymerization reaction and preparation method of consolidated abrasive grinding pad
CN114952608A
Coated abrasive article and method of making same
CA2264779A1
Epoxy resin type diamond grinding pad and manufacturing method thereof
CN103465155A
LED-UV (Light Emitting Diode-Ultraviolet) curing nano-coating for woodenware and preparation method thereof
CN107513344A